UMP Foundation to give aid to students - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2020)
PEKAN: Universiti Malaysia Pahang (UMP) students who were forced to postpone their travel plans to return to campus will receive RM100 emergency cash aid each.